2010
DOI: 10.1902/jop.2010.100039
|View full text |Cite
|
Sign up to set email alerts
|

Compliance as a Prognostic Indicator. II. Impact of Patient's Compliance to the Individual Tooth Survival

Abstract: Complete patient compliance with increased frequency of periodontal maintenance is important for improved dental prognosis through reduction of tooth loss among molars and minimization of alveolar bone loss among non-molars.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
33
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 22 publications
4
33
0
Order By: Relevance
“…Our initial PPD values are higher than those observed by Rosling et al, 10 who studied normal (NM 2.5 ± 0.4; M 2.8 ± 0.5) and highly susceptible (NM 2.9 ± 0.6; M 4.0 ± 0.8) individuals. This author, as reported by the present study, also observed higher and significant PPD values for M. Miyamoto et al 11 likewise reported similar results for NM (3.50 mm) and M (4.36 mm).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our initial PPD values are higher than those observed by Rosling et al, 10 who studied normal (NM 2.5 ± 0.4; M 2.8 ± 0.5) and highly susceptible (NM 2.9 ± 0.6; M 4.0 ± 0.8) individuals. This author, as reported by the present study, also observed higher and significant PPD values for M. Miyamoto et al 11 likewise reported similar results for NM (3.50 mm) and M (4.36 mm).…”
Section: Discussionsupporting
confidence: 90%
“…7 For example, increased periodontal probing depth (PPD), clinical attachment loss (CAL) and a higher percentage of missing teeth are observed for M. [8][9][10][11] In this scenario, the initial observations of Nordland et al 12 and Loos et al 13 are particularly important. They compared free surfaces of M and non-molars (NM) with those having furcation involvement and observed that the worst condition was always associated with M. Nevertheless, most studies have not evaluated the response of different teeth to systematic periodontal intervention.…”
Section: Introductionmentioning
confidence: 99%
“…3). One study was excluded from this analysis because of insufficient data (Miyamoto et al 2010). The results demonstrated each patient in the RC group could save approximately 1 more tooth than do the patients in the EC group during an 8-y SPT phase.…”
Section: Synthesis Of Resultsmentioning
confidence: 99%
“…Miyamoto et al [29] raised the question of whether tooth loss should be taken as an evaluation indicator of the treatment effect because the dentist can have a great deal of influence on tooth loss. However, many researchers consider the rate of tooth loss to be an effective evaluation of periodontal treatment [30,31].…”
Section: Discussionmentioning
confidence: 99%